RETIREMENT BENEFIT SCHEME IN UKRAINE: CURRENT REALITIES AND EUROPEAN EXPERIENCE - Loyak, L. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The subject of the study is theoretical and methodological principles of the retirement benefit scheme formation in Ukraine in the context of eurointegration transformations. The purpose of the study is to provide a theoretical substantiation of the essence of Ukraine retirement benefit scheme in the context of European integration transformation, studying the European countries experience in reforming the retirement benefit scheme and the possibilities of its application. Research methods. The study uses a set of scientific methods and approaches, including logical generalization, systemic, method of comparisons, graphical, which allowed to ensure the conceptual unity of research. Results of work. The article deals with the actual approaches to the «retirement benefit scheme» concept definition, substantiates its essence, defines the methods of social protection and features of the construction of the national pension system in European countries. The problems and perspectives of development of the modern pension system of Ukraine as an important component of the population social security are researched. The attention is focused on the problems of reducing the payment of pension contributions, raising the retirement age and developing non-state pension funds. The field of results application. In the field of economics and in the practical activities of the structural units of the Pension Fund of Ukraine. Conclusions. The main results of the study and its theoretical and methodological results can be reduced to the following wording: the retirement benefit scheme in each country is an important component of social protection of the population, and the effectiveness of this system depends on the welfare of the population and the level of stability in society; the pension system of Ukraine does not meet the requirements of the present due to complicated problems, which are caused to some extent by the shortcomings of the existing retirement benefit scheme, the imperfection of the mechanism of its financing. Further study of the European countries experience and successful constructive solutions will be useful for their application in the process of building and reforming our own pension system, which will avoid negative tendencies, caused by socio-economic realities of modern society.